Penyelesaian Tanah Wakaf Di Kecamatan Selebar Perspektif Hukum Islam Dan Hukum Positif - Ibnu Masud; Irsal Irsal (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2022)
Abstract :The purpose of this study is: to analyze and describe the procedures for resolving waqf land disputes in the Selebar District of Bengkulu City, then to analyze and describe the procedures for resolving waqf land disputes in the Selebar District of Bengkulu City in terms of the perspective of Islamic law and positive law. In exploring and obtaining information in the field, the researchers used field research with a qualitative descriptive approach. This research was started from May to June 2021, which was located in Selebar District, Bengkulu City, Bengkulu Province, Indonesia. In the study, it was found that the parties had taken steps to resolve waqf land disputes including through Deliberation, Arbitration, Mediation and Litigation, the implementation of which was adjusted to the situation and conditions at the time of the dispute. Furthermore, in the settlement of waqf land disputes in Selebar District, Bengkulu city, Nazir and the disputing parties prefer to use the peaceful way. From several cases and data obtained that the settlement of waqf land disputes in Selebar District, Bengkulu City, the authors can conclude that: Settlement of disputes through non-litigation and litigation channels is in accordance with Islamic law and positive law. The settlement of waqf land disputes in the Selebar District of Bengkulu City has been in accordance with the provisions of Islamic law and positive law.Keywords: Waqf Land Dispute, Broad, Positive Law and Islamic Law.Abstrak : Tujuan penelitian ini adalah: untuk menganalisis dan mendeskripsikan tata cara penyelesaian sengketa tanah wakaf di Kecamatan Selebar Kota Bengkulu, selanjutnya untuk menganalisis dan mendeskripsikan tata cara penyelesaian sengketa tanah wakaf di Kecamatan Selebar Kota Bengkulu ditinjau dari perspektif hukum Islam dan hukum positif. Dalam menggali dan mendapatkan informasi dilapangan maka peneliti menggunakan penelitian lapangan (field research) dengan pendekatan deskriptif kualitatif. Penelitian ini dimulai bulan Mei sampai dengan bulan Juni 2021 yang berlokasi di Kecamatan Selebar Kota Bengkulu Provinsi Bengkulu Indonesia. Dalam penelitian ditemukan bahwa para pihak telah melakukan cara dalam menyelesaikan sengketa tanah wakaf diantaranya melalui Musyawarah, Arbitrase, Mediasi dan Litigasi yang pelaksanaannya disesuaikan dengan situasi dan kondisi pada saat terjadi sengketa. Selanjutnya dalam penyelesaian sengketa tanah wakaf di Kecamatan Selebar kota Bengkulu, Nazir dan para pihak yang bersengketa lebih memilih menggunakan jalan damai. Dari beberapa kasus dan data yang didapat bahwa penyelesaian sengketa tanah wakaf di Kecamatan Selebar Kota Bengkulu, dapat penulis simpulkan bahwa: Penyelesaian sengketa melalui jalur non litigasi dan litigasi sesuai dengan hukum Islam dan hukum positif. Penyelesaian sengketa tanah wakaf di Kecamatan Selebar Kota Bengkulu telah sesuai dengan ketentuan hukum Islam dan hukum Positif.Kata kunci : Sengketa Tanah Wakaf, Selebar, Hukum Positif dan Hukum Islam.